2003
DOI: 10.1126/science.1082703
|View full text |Cite
|
Sign up to set email alerts
|

The 2002 Denali Fault Earthquake, Alaska: A Large Magnitude, Slip-Partitioned Event

Abstract: The MW (moment magnitude) 7.9 Denali fault earthquake on 3 November 2002 was associated with 340 kilometers of surface rupture and was the largest strike-slip earthquake in North America in almost 150 years. It illuminates earthquake mechanics and hazards of large strike-slip faults. It began with thrusting on the previously unrecognized Susitna Glacier fault, continued with right-slip on the Denali fault, then took a right step and continued with right-slip on the Totschunda fault. There is good correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
302
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(321 citation statements)
references
References 19 publications
17
302
1
1
Order By: Relevance
“…As discussed above (results of the synthetic C2), this behavior suggests that the section of the rupture that corresponds to the first 5 s is bilateral. This conclusion is consistent with the models presented by Eberhart-Phillips et al (2003) or Dunham and Archuleta (2004), who describe this rupture with emerging bilateral to unilateral change after the first few seconds. The next ∼50 s shows a unilateral rupture, with a length estimated to be 273 km toward the ESE with an azimuth of γ = 112 ± 7.27 • .…”
Section: Fig 22supporting
confidence: 81%
See 2 more Smart Citations
“…As discussed above (results of the synthetic C2), this behavior suggests that the section of the rupture that corresponds to the first 5 s is bilateral. This conclusion is consistent with the models presented by Eberhart-Phillips et al (2003) or Dunham and Archuleta (2004), who describe this rupture with emerging bilateral to unilateral change after the first few seconds. The next ∼50 s shows a unilateral rupture, with a length estimated to be 273 km toward the ESE with an azimuth of γ = 112 ± 7.27 • .…”
Section: Fig 22supporting
confidence: 81%
“…20 and Table 7. These intervals correspond mainly to the first and second sections of the rupture along the Susitna Glacier fault and Denali fault, as observed in other studies (e.g., Eberhart-Phillips et al 2003;Ozacar and Beck 2004). The results showed that the first ∼5 s (D1) are derived from a dataset that does not produce a good fit to the theoretical model (Fig.…”
Section: Fig 21mentioning
confidence: 58%
See 1 more Smart Citation
“…Variations in the slip distribution along seismically active terrestrial faults are common (e.g., Sieh et al, 1993;Jónsson et al, 2002;EberhartPhillips et al, 2003). Slip distributions are often asymmetric or heterogeneous with varying amounts of slip occurring on different sections of the fault (Hernandez et al, 1999;Eberhart-Phillips et al, 2003). Thus, the distribution of slip on the fault segments necessary to best fit the topography of the wrinkle ridges may reflect the accumulation of different amounts of slip on fault segments as the structures developed.…”
Section: Mechanical Modelingmentioning
confidence: 99%
“…during the 3 November, 2002, Alaska earthquake where several rockslides were triggered which themselves triggered mud/debris flows, partly also on glaciers but without entraining entire glaciers (Ebehart-Phillips et al, 2003). Hypothesis (2.)…”
Section: Assessment and Interpretationmentioning
confidence: 99%